The Integration of Islamic Educational Values from the Qur'an and Hadith into English Language Teaching: A Literature Review - Rizdki Elang Gumelar; Dedeh Jubaedah (Journal of English Education Studies, 2025)
This study explores the integration of Islamic educational values into English language teaching by analyzing relevant literature from the Qur'an, Hadith, and educational sources. Islamic values such as honesty, responsibility, tolerance, and diligence serve not only as moral foundations but also as character-building principles that can enhance the learning experience. The study adopts a qualitative approach using library research methods to identify, analyze, and synthesize Islamic teachings that align with effective English teaching practices. The findings indicate that these values can be incorporated across the four key language skills: reading, speaking, writing, and listening—through Islamic-themed texts, dialogue topics, reflective essays, and audio-visual materials rooted in Islamic ethics. Rather than replacing existing curricula, this integration embeds religious values into instructional content, making language learning more meaningful by addressing not only linguistic and cognitive development but also affective and spiritual growth. The study recommends the development of curricula and teaching materials that are thematically aligned with Islamic values. This approach supports the formation of Muslim learners who are globally competent in English while maintaining a strong Islamic identity. Further empirical research is encouraged to validate and refine this integrative model in formal educational settings.